Does Nitrate Enrichment Accelerate Organic Matter Turnover in Subterranean Estuaries? - Ibánhez, J. Severino P.; Álvarez-Salgado, Xosé Antón; Rocha, Carlos (Frontiers in Marine Science, 2021)
Due to the widespread pollution of coastal groundwaters with fertilizers, submarine groundwater discharge (SGD) is often thought to be a large dissolved inorganic nitrogen (DIN) source to the ocean. Whether this N is autochthonous or allochthonous to the subterranean estuary (STE), the availability of large quantities of DIN can nevertheless interact with the cycling of other elements, such as carbon (C). In previous studies, we documented the discharge of large quantities of freshwater and NO3- from the mouth of an STE into the Ria Formosa lagoon (SW Iberian Peninsula). For the period covered in this study (2009-2011), the same STE site was dominated by recirculating seawater due to a prolonged fall in piezometric head in the coupled coastal aquifers. Total SGD rates remained similarly high, peaking at 144 cm day-1 at the lower intertidal during fall. We observed a progressive increase of NO3- availability within the STE associated with the recovery of piezometric head inland. Interestingly, during this period, the highest SGD-derived dissolved organic C and DIN fluxes (112±53 and 10±3 mmol m-2 d-1 respectively) originated in the lower intertidal. NO3- enrichment in the STE influences the benthic reactivity of fluorescent dissolved organic matter (FDOM): when seawater recirculation drives STE dynamics, only small changes in the benthic distribution of recalcitrant humic-like FDOM are observed (from -2.57±1.14 to 1.24±0.19 10-3 R.U. “bulk” sediment h-1) in the absence of DIN. However, when DIN is available, these recalcitrant fractions of FDOM are actively generated (from 1.32±0.15 to 11.56±3.39 10-3 R.U. “bulk” sediment h-1), accompanied by the production of labile protein-like FDOM. The results agree with previous studies conducted with flow-through reactor experiments at the same site and suggest that DIN enrichment in the STE enhances the metabolic turnover of sedimentary organic matter up to the point of discharge to surface waters. DIN pollution of coastal aquifers may therefore promote a contraction of the residence time of particulate organic C within the STE, driving carbon from continental storage into the sea.